선별검사자료를 이용한 백내장 유병률의 추정 - 송기준; Ki Jun Song; 한무영; Moo Young Han; 김신영; Shin Young Kim; 하정윤; Jung Yoon Ha; 김응권; Eung Kwon Kim (Daihan angwa haghoi jabji, 2007)
목적 : 선별검사자료를 이용하여 통계학적 모형에 기초한 백내장의 유병률을 보다 효율적으로 추정하고자 하였다. 대상과 방법 : 선별검사자료와 병원진료자료를 이용하여 2×3 형식의 표와 같이 미분류군을 포함하는 상황으로 자료를 정리했을 때, 최대우도추정방법을 이용하여 선별검사결과 양성, 음성과 백내장 존재 유,무로만 구분되는 2×2 형식의 표를 구하고 그 때 유병률을 추정하였다. 이 방법을 1994 년 6월부터 2005년 9월까지 건강검진을 받은 20세 이상의 85,505명의 선별검사자료에 적용하였다. 결과 : 백내장 유병률의 추정치는 전체에서 13.98%였고, 이 때 남자는 15.29% 여자는 12.97%로 추정되었다. 또한 연령별로 구분하여 얻어낸 유병률의 추정치에서 60세 이상으로 갈수록 유병률이 급격히 높아지는 것을 알 수 있었다. 결론 : 본 연구에서 제안된 유병률 추정방법을 통해 얻은 결과는 기존의 연구들과 비교할 때 그 타당성을 확보할 수 있었고, 백내장은 고연령에서 급격하게 증가하고 있다는 사실에서 예방과 조기발견 및 적절한 치료가 필요하다고 여겨진다. <한안지 48(6):768-773, 2007> Purpose: To estimate the prevalence of cataracts based on screening test results and statistical estimation methods. Methods: Between June 1994 and September 2005, 85,505 persons aged 20 years and older were screened at a health promotion center for a general health care screen. We assumed that all subjects had complete screening results; however some subjects had an unknown disease status. A 2×3 table form could be generated from this data set. To estimate cataract prevalence, we used a maximum likelihood estimation method to reconstruct a 2×2 table including probabilities for each cell. Results: The overall estimated cataract prevalence was 13.98% (95% confidence intervals, 13.75% to 14.21%). We estimated the prevalence of cataracts to be 15.29% in men (95% confidence intervals, 14.95% to 15.63%) and 12.97% in women (95% confidence intervals, 12.65% to 13.29%). In addition, we found that the cataract prevalence distinctly increased in people aged 60 years or older. Conclusions: We found that these estimated cataract prevalences were not considerably different from study results obtained in other countries. Therefore, our method may be considered to be appropriate for estimating prevalence. Our results indicate that cataract prevalence in our study population increases with age and highlight the need for early detection and early interventions. J Korean Ophthalmol Soc 48(6):768-773, 2007